Economics for environmental professionals - Spellman, Frank R. (Taylor & Francis, 2015)
Economics for Environmental Professionals provides a fully explanatory, quantitative, and practical introduction to a wide range of topics that make up the science of environmental economics. Moreover, it showcases the power of economic principles to explain and predict issues and current events impacting the environment. It discusses the economics relevant to the environmental mediums of air, water, and land and provides pertinent information on air toxics, hazardous wastes, and other related topics. It provides environmental professionals with the education not only to understand the nuts and bolts of economic analysis but also to conduct economic analyses